Composite catalyst and application thereof in preparation of paraformaldehyde

By using composite catalysts, the active metal and the support work together, the problems of low polymerization, low yield and poor stability of paraformaldehyde are solved, and efficient and stable preparation of paraformaldehyde is achieved, reducing production costs.

CN119838628AActive Publication Date: 2025-04-18WEIFANG HUIFENG CHEM IND CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510339219.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

In the prior art, the polymerization degree, low yield, and poor product stability when preparing paraformaldehyde.

Method used

A composite catalyst is used, consisting of active metals and support, which reduces formaldehyde molecular activity through metal bonding, and uses the weak acidity of the support to seal the polymer end groups and improve product stability.

Benefits of technology

It improves the polymerization degree and yield of paraformaldehyde, enhances the stability of the product, and reduces production costs and equipment corrosion risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838628A_ABST
    Figure CN119838628A_ABST
Patent Text Reader

Abstract

The invention discloses a composite catalyst and application thereof in preparation of paraformaldehyde, the catalyst is composed of active metal and a carrier, the active metal is uniformly distributed on the surface of the carrier, metal ions and formaldehyde molecules are combined through metallic bonds, the activity of the formaldehyde molecules is reduced, and generation of high polymers is avoided; the carrier can support active components and can form a synergistic catalysis effect with active metal due to the weak acidity of the carrier, so that the terminal group of a polymer can be sealed when the polymerization degree of paraformaldehyde reaches a certain degree, and residual water is dissociated and quickly evaporated and dried; the catalyst is prepared through an impregnation method, the preparation method is simple and can be recycled, and the production cost is reduced; compared with the prior art, the method provided by the invention has the advantages that the system does not use an acidic or alkaline auxiliary agent and does not corrode equipment, the production investment is reduced, the production cost is further reduced, and the paraformaldehyde prepared by the method provided by the invention is low in polymerization degree, high in yield and high in product stability. The invention belongs to the technical field of chemical engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of chemical technology, and in particular to a composite catalyst and its application in the preparation of paraformaldehyde. Background Art

[0002] Low-polymerization degree paraformaldehyde (PF) is an important chemical raw material in industry. It has the characteristics of high aldehyde content, good water solubility, complete depolymerization, loose products, uniform particles, etc. It is easy to store and transport. It is an ideal substitute for industrial formaldehyde and is widely used in chemical, pharmaceutical, pesticide, coating, resin synthesis and other fields, especially in the field of synthesis that requires the use of anhydrous or high-concentration formaldehyde as a raw material; because ordinary industrial formaldehyde contains more than 60% water, it not only increases the transportation volume and cost, but also increases the equipment investment, reduces the reaction speed, and increases energy and material consumption in the production of chemical products due to the presence of water; according to relevant data, the use of paraformaldehyde instead of industrial formaldehyde to produce resin reduces material consumption by more than 10%, and for every ton of formaldehyde consumed, the steam consumption decreases by 1.5-2 tons. Low-polymerization degree paraformaldehyde in my country is mainly used in the production of herbicides, insecticides, fungicides and fumigants, accounting for about 70% of the total consumption of paraformaldehyde, with an annual total demand of about 50,000 tons, of which more than 80% depends on imports.

[0003] At present, the more mature production process routes of paraformaldehyde used at home and abroad are mainly the following: 1. The process of producing polyformaldehyde by vacuum rake dryer has the following disadvantages: there are dead corners, the discharge is troublesome, and the product is in a lump form and difficult to crush. The production cycle is long. It is a traditional old production process and has been basically eliminated abroad. Currently, only a few manufacturers in China use this method to produce PF; 2. The process of producing polyformaldehyde by metal conveyor belt drying has the following disadvantages: it occupies a large area, is noisy during operation, the product needs to be crushed, and granular polyformaldehyde cannot be obtained directly; 3. The spray method has the following disadvantages: it is difficult to separate gas and solid, it is difficult to recover fine particles of dust, the thermal efficiency is not high, and the equipment volume is large; 4. The azeotropic distillation method has only a few manufacturers currently producing it due to the types of azeotropes, recovery, and process amplification.

[0004] According to literature reports, common problems in the production of polyformaldehyde include: when formaldehyde is heated and dehydrated, polymerization and depolymerization occur simultaneously, formaldehyde is easily volatilized and lost, and the yield is low; due to the low aldehyde content and high water content, the product is sticky and easy to agglomerate; the stability and water solubility are poor, mainly because during the storage of the product, the presence of some polar substances (trace amounts of water and other impurities) will cause polyformaldehyde to continue to polymerize, resulting in a high degree of polymerization, a large molecular weight, and difficulty in dissolving; in addition, the product contains a small amount of formic acid and methanol, and a certain amount of insoluble polyformaldehyde esters will be produced under the catalysis of formic acid.

[0005] The key to preparing paraformaldehyde is to control the degree of polymerization of the product, prevent formaldehyde from highly polymerized, shorten the drying and dehydration time, and improve the product yield. Therefore, some effective strategies need to be adopted to improve the yield of formaldehyde polymerization reaction and improve the stability of paraformaldehyde. Summary of the invention

[0006] The purpose of the present application is to provide a composite catalyst and its application in the preparation of paraformaldehyde, so as to solve the technical problems of low polymerization degree, low yield and poor product stability of paraformaldehyde in the preparation process in the prior art.

[0007] To achieve the above object, the technical solution adopted in the present application is: to provide a method for preparing a composite catalyst, which specifically comprises the following steps: Add metal salt to deionized water, add carrier after dissolving, mix, stir and dry to obtain composite catalyst; The metal salt is one or more of Fe hydrochloride, sulfate, nitrate, acetylacetonate and hydrate thereof; The carrier is one or more of SiO2 molecular sieve, Al2O3 molecular sieve, HZSM-5 molecular sieve and Hβ molecular sieve.

[0008] In one embodiment, The mass ratio of the metal element mass of the metal salt to the mass ratio of the carrier is 0.03-0.09:1.

[0009] In one embodiment, The mixing temperature is 40-60°C.

[0010] In one embodiment, The stirring time is 4-6 h.

[0011] In one embodiment, The metal salt is specifically one or more of ferric chloride hexahydrate (FeCl3·6H2O), ammonium ferric sulfate dodecahydrate (NH4Fe(SO4)2·12H2O), ferrous sulfate heptahydrate (FeSO4·7H2O), ferric chloride (FeCl3), ferric nitrate nonahydrate (Fe(NO3)3·9H2O), ferrous chloride (FeCl2), ferric triacetylacetonate (Fe(acac)3) or ferric sulfate (Fe2(SO4)3).

[0012] The present application also provides an application of a composite catalyst in the preparation of paraformaldehyde, which specifically comprises the following steps: adding methanol into a reactor, taking formaldehyde solution as a raw material, and carrying out a polymerization reaction in the presence of the composite catalyst to obtain paraformaldehyde.

[0013] In one embodiment, The mass ratio of the composite catalyst to the formaldehyde solution is 0.01-0.07:1.

[0014] In one embodiment, The polymerization temperature is 60-120°C, and the polymerization time is 1-3 h.

[0015] In one embodiment, The mass ratio of methanol to formaldehyde solution is 1:1.

[0016] In one embodiment, The concentration of formaldehyde solution is 37-75%.

[0017] The present application provides a method for preparing a composite catalyst, which consists of an active metal and a carrier, wherein the active metal is uniformly distributed on the surface of the carrier, and the metal ions and formaldehyde molecules are combined through metal bonds, thereby reducing the activity of the formaldehyde molecules and avoiding the formation of polymers; in addition to carrying the active components, the carrier can form a synergistic catalytic effect with the active metal due to its own weak acidity, and can seal the end groups of the polymer when the polymerization degree of polyformaldehyde reaches a certain level, so that the residual water is freed and quickly evaporated and dried; the catalyst is prepared by an impregnation method, the preparation method is simple, can be recycled and reused, and the production cost is reduced; the present application also provides the use of the composite catalyst in the preparation of polyformaldehyde, and this method does not use acidic or alkaline additives, does not corrode equipment, reduces production investment, and further reduces production costs, and the polyformaldehyde prepared by the method provided by the present invention has a low polymerization degree, a high yield, and high product stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0019] Figure 1 This is an electron microscope photograph of the composite catalyst. DETAILED DESCRIPTION

[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clear, the present application is further described in detail. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0021] Example 1 (i) Add 4.84 g FeCl3·6H2O to 50 ml deionized water. After it is completely dissolved, add 20 g HZSM-5 molecular sieve. Heat to 40 °C and stir for 5 h. Remove excess water by evaporation. After fully drying, obtain a composite catalyst, which is designated as catalyst #1. Its structural characterization is shown in the following table. Figure 1 As shown, instrument model: JEOL JSM-6701F, magnification 5000 times; (ii) In a reaction container, 100 g of 37% formaldehyde solution and 1.85 g of 1# catalyst were added in sequence. After the temperature was raised to 80°C, 100 g of methanol was added and the mixture was stirred to carry out polymerization reaction. The reaction was kept warm for 2 h to obtain a reaction product. The reaction product was pumped to a multi-stage fluidized bed series spray drying system for drying to obtain polyformaldehyde solid particles. The final product had a polyformaldehyde content of 93.2% and a degree of polymerization of 10. After being stored at room temperature for 90 days, the solubility of the product in water was 100%.

[0022] Example 2 The difference between this embodiment and embodiment 1 is that FeCl3·6H2O is replaced by NH4Fe(SO4)2·12H2O, and the added amount of NH4Fe(SO4)2·12H2O is 8.634 g, which is recorded as catalyst 2#. The polymerization reaction is carried out using catalyst 2#. The final product has a polyformaldehyde content of 93.0% and a degree of polymerization of 14. After being stored at room temperature for 90 days, the solubility of the product in water is 100%.

[0023] Example 3 The difference between this embodiment and embodiment 1 is that FeCl3·6H2O is replaced by FeSO4·7H2O, and the added amount of FeSO4·7H2O is 4.978 g, which is recorded as catalyst #3. The polymerization reaction is carried out using catalyst #3. The final product has a paraformaldehyde content of 94.3% and a polymerization degree of 9. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0024] Example 4 The difference between this embodiment and embodiment 3 is that in step (ii), the concentration of the formaldehyde solution is 50%, the amount of catalyst #3 added is 2.5 g, the final product has a paraformaldehyde content of 95.5%, a degree of polymerization of 14, and after being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0025] Example 5 The difference between this embodiment and embodiment 3 is that in step (ii), the concentration of the formaldehyde solution is 75%, the amount of catalyst #3 added is 3.75 g, the final product has a paraformaldehyde content of 95.9%, a degree of polymerization of 16, and after being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0026] Example 6 The difference between this embodiment and embodiment 3 is that in step (ii), the amount of catalyst #3 added is 0.37 g, the final product has a paraformaldehyde content of 92.6%, a degree of polymerization of 16, and after being stored at room temperature for 90 days, the solubility of the product in water is 100%.

[0027] Example 7 The difference between this embodiment and embodiment 3 is that in step (ii), the amount of catalyst #3 added is 1.11 g, the final product has a paraformaldehyde content of 93.6%, a degree of polymerization of 12, and after being stored at room temperature for 90 days, the solubility of the product in water is 100%.

[0028] Example 8 The difference between this embodiment and embodiment 3 is that in step (ii), the amount of catalyst #3 added is 2.59 g, the final product has a paraformaldehyde content of 95.5%, a degree of polymerization of 14, and after being stored at room temperature for 90 days, the solubility of the product in water is 100%.

[0029] Example 9 The difference between this embodiment and embodiment 3 is that in step (ii), after adding catalyst #3, the temperature is raised to 60°C, the final product has a paraformaldehyde content of 94.1%, a degree of polymerization of 10, and after being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0030] Example 10 The difference between this embodiment and embodiment 3 is that in step (ii), after adding catalyst #3, the temperature is raised to 100°C, and the final product has a polyformaldehyde content of 95.5% and a degree of polymerization of 20. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0031] Embodiment 11 The difference between this embodiment and embodiment 3 is that in step (ii), after adding catalyst #3, the temperature is raised to 120°C, and the final product has a paraformaldehyde content of 96.6% and a degree of polymerization of 25. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0032] Example 12 The difference between this embodiment and embodiment 3 is that the polymerization reaction time in step (ii) is 1 h, the polyformaldehyde content of the final product is 93.7%, the degree of polymerization is 9, and after being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0033] Embodiment 13 The difference between this embodiment and embodiment 3 is that the polymerization reaction time in step (ii) is 3 h, the polyformaldehyde content of the final product is 95.4%, the degree of polymerization is 14, and after being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0034] Embodiment 14 The present embodiment is different from the embodiment 1 in that FeCl3·6H2O is replaced by Fe2(SO4)3, the added amount of Fe2(SO4)3 is 7.16 g, and is denoted as catalyst #4. The polymerization reaction is carried out using catalyst #4, and the final product has a paraformaldehyde content of 94.1% and a polymerization degree of 10. After being stored at room temperature for 90 days, the solubility of the product in water is 100%.

[0035] Embodiment 15 The present embodiment is different from the embodiment 1 in that FeCl3·6H2O is replaced by FeCl3, and the amount of FeCl3 added is 2.904 g, which is recorded as catalyst #5. The polymerization reaction is carried out using catalyst #5, and the final product has a paraformaldehyde content of 94.4% and a degree of polymerization of 12. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0036] Example 16 The difference between this embodiment and embodiment 1 is that FeCl3·6H2O is replaced by Fe(NO3)3·9H2O, and the added amount of Fe(NO3)3·9H2O is 7.234 g, which is recorded as catalyst #6. Catalyst #6 is used for polymerization reaction. The final product has a polyformaldehyde content of 93.6% and a polymerization degree of 10. After being stored at room temperature for 90 days, the solubility of the product in water is 100%.

[0037] Embodiment 17 The present embodiment is different from the embodiment 1 in that FeCl3·6H2O is replaced by FeCl2, and the amount of FeCl2 added is 2.269 g, which is denoted as catalyst #7. The polymerization reaction is carried out using catalyst #7, and the final product has a paraformaldehyde content of 93.8% and a degree of polymerization of 14. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0038] Embodiment 18 The present embodiment is different from the embodiment 1 in that FeCl3·6H2O is replaced by Fe(acac)3, and the added amount of Fe(acac)3 is 6.324 g, which is denoted as catalyst #8. The polymerization reaction is carried out using catalyst #8, and the final product has a paraformaldehyde content of 93% and a polymerization degree of 16. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0039] Embodiment 19 The present embodiment is different from the embodiment 3 in that the HZSM-5 molecular sieve is replaced with a SiO2 molecular sieve, which is denoted as catalyst #9. The polymerization reaction is carried out using catalyst #9. The final product has a paraformaldehyde content of 93.2% and a degree of polymerization of 16. After being stored at room temperature for 90 days, the solubility of the product in water is 100%.

[0040] Embodiment 20 The present embodiment is different from the embodiment 3 in that the HZSM-5 molecular sieve is replaced with an Al2O3 molecular sieve, which is denoted as catalyst #10. The polymerization reaction is carried out using catalyst #10. The final product has a paraformaldehyde content of 93.5% and a degree of polymerization of 14. After being stored at room temperature for 90 days, the solubility of the product in water is 100%.

[0041] Embodiment 21 The present embodiment is different from the embodiment 3 in that the HZSM-5 molecular sieve is replaced with Hβ molecular sieve, which is denoted as catalyst #11. The polymerization reaction is carried out using catalyst #11. The final product has a paraformaldehyde content of 94.1% and a polymerization degree of 16. After being stored at room temperature for 90 days, the solubility of the product in water is 100%.

[0042] Embodiment 22 The difference between this embodiment and embodiment 3 is that the amount of FeSO4·7H2O added is 2.987 g, which is recorded as catalyst #12. The polymerization reaction is carried out using catalyst #12. The final product has a paraformaldehyde content of 94.1% and a polymerization degree of 16. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0043] Embodiment 23 The difference between this embodiment and embodiment 3 is that the amount of FeSO4·7H2O added is 6.969 g, which is denoted as catalyst #13. The polymerization reaction is carried out using catalyst #13. The final product has a paraformaldehyde content of 95.2% and a polymerization degree of 10. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0044] Embodiment 24 The difference between this embodiment and embodiment 3 is that the amount of FeSO4·7H2O added is 8.96 g, which is denoted as catalyst #14. The polymerization reaction is carried out using catalyst #14. The final product has a paraformaldehyde content of 95.7% and a polymerization degree of 10. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0045] Embodiment 25 The difference between this embodiment and embodiment 3 is that in step (i), the temperature is raised to 50°C after the molecular sieve is added, which is denoted as catalyst #15. The polymerization reaction is carried out using catalyst #15. The final product has a paraformaldehyde content of 94% and a degree of polymerization of 10. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0046] Embodiment 26 The difference between this embodiment and embodiment 3 is that in step (i), the temperature is raised to 60°C after the molecular sieve is added, which is denoted as catalyst #16. The polymerization reaction is carried out using catalyst #16. The final product has a paraformaldehyde content of 94.1% and a degree of polymerization of 10. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0047] Embodiment 27 The difference between this embodiment and embodiment 3 is that in step (i), the time of heat preservation and stirring is 4 hours, and catalyst #17 is used for the polymerization reaction. The final product has a paraformaldehyde content of 94% and a degree of polymerization of 16. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0048] Embodiment 28 The difference between this embodiment and embodiment 3 is that in step (i), the time of heat preservation and stirring is 6 hours, and the polymerization reaction is carried out using catalyst #18. The final product has a polyformaldehyde content of 94.1% and a degree of polymerization of 14. After being placed at room temperature for 90 days, the solubility of the product in water is 100%.

[0049] Embodiment 29 Catalyst application example: Catalyst 3# is loaded into a fixed bed reactor and heated to 80°C and kept warm; at room temperature, 1200 g of 37% formaldehyde solution and 1200 g of methanol are configured into a mixed solution and preheated to 60°C, and the preheated mixed solution is passed into the fixed bed reactor at a flow rate of 20 ml / min. After 2 hours of cyclic reaction, the material is discharged and pumped to a multi-stage fluidized bed series spray drying system for drying to obtain polyformaldehyde solid particles. The final product has a polyformaldehyde content of 94.2% and a degree of polymerization of 9. After 90 days at room temperature, the solubility of the product in water is 100%.

[0050] Comparative Example 1 In a reaction container, 100 g of 37% formaldehyde solution and 1.85 g of HZSM-5 molecular sieve were added in sequence. After the temperature was raised to 80°C, 100 g of methanol was added, the mixture was stirred and mixed, and the reaction was kept warm for 2 h to obtain a reaction product. The reaction product was pumped to a multi-stage fluidized bed series spray drying system for drying to obtain polyformaldehyde solid particles. The final product had a polyformaldehyde content of 94.8% and a degree of polymerization of 35. After being placed at room temperature for 90 days, the solubility of the product in water was 80%.

[0051] Comparative Example 2 In a reaction container, 100 g of 37% formaldehyde solution and 1.85 g of FeSO4·7H2O were added in sequence. After the temperature was raised to 80°C, 100 g of methanol was added, the mixture was stirred and mixed, and the reaction was carried out for 2 h at a temperature preservation temperature to obtain a reaction product. The reaction product was pumped to a multi-stage fluidized bed series spray drying system for drying to obtain polyformaldehyde solid particles. The final product had a polyformaldehyde content of 95.3% and a degree of polymerization of 40. After being placed at room temperature for 90 days, the solubility of the product in water was 75%.

[0052] It can be seen from Examples 1-28 and Comparative Examples 1-2 that adding only a carrier or a metal salt does not produce as good an effect as the composite catalyst.

[0053] The present application provides a method for preparing a composite catalyst, wherein a metal salt is added to deionized water, and after dissolving, a carrier is added, and the composite catalyst is obtained after mixing, stirring and drying. The catalyst is composed of an active metal and a carrier, wherein the active metal is evenly distributed on the surface of the carrier, and the metal ions and formaldehyde molecules are combined through metal bonds to reduce the activity of the formaldehyde molecules and avoid the formation of polymers. In addition to carrying the active component, the carrier can form a synergistic catalytic effect with the active metal due to its own weak acidity, and can seal the end groups of the polymer when the polymerization degree of polyformaldehyde reaches a certain degree, so that the residual water is freed and quickly evaporated and dried. The catalyst is prepared by an impregnation method, and the preparation method is simple, recyclable and reusable, thereby reducing the production cost. The present application also provides an application of the composite catalyst in the preparation of polyformaldehyde, wherein a polymerization reaction is carried out in the presence of the composite catalyst using a formaldehyde solution as a raw material in a reactor to obtain polyformaldehyde. The method does not use an acidic or alkaline auxiliary agent, does not corrode equipment, reduces production investment, and further reduces production costs. The polyformaldehyde prepared by the method provided by the present invention has a low polymerization degree, a high yield, and high product stability.

[0054] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0055] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a composite catalyst, characterized in that: The specific steps include: Add metal salt to deionized water, add carrier after dissolving, mix, stir and dry to obtain composite catalyst; The metal salt is one or more of Fe hydrochloride, sulfate, nitrate, acetylacetonate and hydrate thereof; The carrier is one or more of SiO2 molecular sieve, Al2O3 molecular sieve, HZSM-5 molecular sieve and Hβ molecular sieve.

2. The method for preparing a composite catalyst according to claim 1, characterized in that: The mass ratio of the metal element mass of the metal salt to the mass ratio of the carrier is 0.03-0.09:

1.

3. The method for preparing a composite catalyst according to claim 1, characterized in that: The mixing temperature is 40-60°C.

4. The method for preparing a composite catalyst according to claim 1, characterized in that: The stirring time is 4-6 h.

5. The method for preparing a composite catalyst according to claim 1, characterized in that: The metal salt is specifically one or more of ferric chloride hexahydrate, ammonium ferric sulfate dodecahydrate, ferrous sulfate heptahydrate, ferric chloride, ferric nitrate nonahydrate, ferrous chloride, ferric triacetylacetonate or ferric sulfate.

6. Use of a composite catalyst in the preparation of paraformaldehyde, characterized in that: The method specifically comprises the following steps: adding methanol into a reactor, taking formaldehyde solution as a raw material, and carrying out polymerization reaction in the presence of a composite catalyst to obtain polyformaldehyde.

7. Use of a composite catalyst according to claim 6 in the preparation of paraformaldehyde, characterized in that: The mass ratio of the composite catalyst to the formaldehyde solution is 0.01-0.07:

1.

8. Use of a composite catalyst according to claim 6 in the preparation of paraformaldehyde, characterized in that: The polymerization reaction temperature is 60-120° C., and the polymerization reaction time is 1-3 h.

9. Use of a composite catalyst according to claim 6 in the preparation of paraformaldehyde, characterized in that: The mass ratio of the methanol to the formaldehyde solution is 1:

1.

10. Use of a composite catalyst according to claim 6 in the preparation of paraformaldehyde, characterized in that: The concentration of the formaldehyde solution is 37-75%.

Citation Information

Patent Citations

  • Synthetic method of polymethoxy dimethylether

    CN103288607A

  • Method of synthesizing trioxymethylene by catalyzing formaldehyde through acid and salt

    CN105175389A

  • Catalyst for synthesizing 3-methyl-3-buten-1-ol and preparation method and use of catalyst

    CN109317212A

  • Method for preparing aldehyde by catalytic oxidation of alcohol with composite metal catalyst

    CN113731440A

  • Porous graphene loaded ferrocobalt sulfide catalyst as well as preparation method and application thereof

    CN113764689A